(Remote) Teaching practices as accompaniment in first year of the initial teaching formation, in unprecedented times (Praxis Educativa, 2021)
This article approaches entrance to higher education, in teaching formation programs, and seeks to find possibilities of intervention as regards drops in this level. We are interested in getting back an experience in process, among groups of early years students, which promotes academic accessibility in these times of sanitary emergency. From a sociocritical perspective in education we recover contributions from Birgin (2015), Ezcurra (2011) and Bourdieu (2007) to reflect on higher education entrance, in which inequalities -originated at lower levels- are reproduced, together with negative views translated into practices, and the absence of certain necessary habitus to be able to go through the teaching formation. It is interesting to register the analysis in an unprecedented present, from the irruption of virtual education, which has led to the resignification of bonds and group work in learning and teaching.
Keywords: teacher formation; accompaniment practices; academic accessibility